The puppet masters - Heinlein, Robert A. (Robert Anson), 1907-1988 (Baen, 2010)
When alien slugs with mind control abilities begin infecting people, Sam and Mary, federal agents whose work is only known to the President, try to stop the invasion and kill the aliens without harming their hosts.